Antioxidant and toxicity assays of ipomoea batatas / Ali Ammar Jamaludin - Jamaludin, Ali Ammar (Faculty of Applied Sciences, 2015)
A study has being conducted on Ipomoea batatas obtained from wet market of Kuala Pilah, Negeri Sembilan. The study aim is to determine the presence of antioxidant properties of Ipomoea batatas by using DPPH assay, which potentially can be used in pharmaceutical and human health. A total of four explant were successfully isolated from Ipomoea batatas and obtained a crude methanolic extract through maceration. All explant such leaves, petioles, roots, and stems were screening for antioxidant activity. Out of four, the highest percentage of scavenging activity was showed by roots (89.04%) followed by leaves (86.37%), petioles (79.82%), and stems (76.84%). Then, all sample of methanolic crude extract were further tested to investigate the toxicity level of Ipomoea batatas by using brine shrimp lethality assay and also determination of lethal concentration LC50 as a standard toxicity indicator. Explant that showed highest lethal concentration LC50 effected in 24 hours was petioles (2.07 mg/ml), followed by stems (2.03 mg/ml) and leaves (1.17 mg/ml). Roots show slightly high toxicity level since the lethal concentration was lowered than 1 mg/ml, which is 0.84 mg/ml. This study show that explant such leaf, stem, and petiole might become the potential sourses since as it have high antioxidant with low toxicity level.